18F-FDG Dynamic PET/CT in Patients with Multiple Myeloma. (June 2015) - Sachpekidis, Christos; Mai, Elias K.; Goldschmidt, Hartmut; Hillengass, Jens; Hose, Dirk; Pan, Leyun; Haberkorn, Uwe; Dimitrakopoulou-Strauss, Antonia
<x xml:space="preserve">Abstract</x> Purpose The value of 18F-FDG PET in the diagnostic approach of multiple myeloma (MM) remains incompletely elicited. Little is known about the kinetics of 18F-FDG in the bone marrow and extramedullary sites in MM. This study aimed to evaluate quantitative data on kinetics and distribution patterns of 18F-FDG in MM patients with regard to pelvic bone marrow plasma cell infiltration. Procedures The study included 40 patients with primary MM. Dynamic PET/CT scanning of the lower lumbar spine and pelvis was performed after the administration of 18F-FDG. Whole-body PET/CT studies were performed. Sites of focal increased tracer uptake were considered as highly suggestive of myelomatous involvement after taking into account the patient history and CT findings. Bone marrow of the os ilium without pathologic tracer accumulation served as reference. The evaluation of dynamic PET/CT studies was based in addition to the conventional visual (qualitative) assessment, on semiquantitative (SUV) calculations, as well as on absolute quantitative estimations after application of a 2-tissue compartment model and a noncompartmental approach. 18F-FDG quantitative information and corresponding distribution patterns were correlated with pelvic bone marrow plasma cell infiltration. Results Fifty-two myelomatous lesions were detected in the pelvis. All parameters in suspected MM lesions ranged in significantly higher levels than in reference tissue (P < 0.01). Correlative analyses revealed that bone marrow plasma cell infiltration rate correlated significantly with SUVaverage, SUVmax, and the parameters K1, influx, and fractal dimension of 18F-FDG in reference bone marrow (P < 0.01). In addition, whole-body static PET/CT imaging demonstrated 4 patterns of tracer uptake; these are as follows: negative, focal, diffuse, and mixed (focal/diffuse) tracer uptake. Patients with a mixed pattern of radiotracer uptake had the highest mean plasma cell infiltration rate in their bone marrow, whereas those with negative PET/CT scans demonstrated the lowest bone marrow plasma cell infiltration. In total, 265 focal myeloma-indicative 18F-FDG–avid lesions were detected, 129 of which correlated with low-dose CT osteolytic findings. No significant correlation between the number of focal lesions detected in PET/CT and bone marrow infiltration was detected. Conclusions The 18F-FDG kinetic parameters K1, influx, and fractal dimension as well as SUVaverage from reference tissue correlated significantly with bone marrow malignant plasma cell infiltration rate. Patients with negative PET/CT demonstrated the lowest bone marrow infiltration by malignant plasma cells, whereas those with a mixed pattern of tracer uptake had the highest infiltration.